AWARENESS OF TURKISH SOCIETY ABOUT ACCESSIBLE TOURISM - Bulgan, Gulay (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2016)
Turkey is among the countries which cannot have a share of accessible tourism although it is challenging and has a big market in tourism. It is required that people with disabilities represent a significant market share and Turkey can have a share of this market to increase its tourism revenues. Aim of this study is to present the awareness level of Turkish society about accessible tourism. This study concluded that Turkish society has an awareness of accessible tourism, but tourism establishments are required to make improvements both in service and in structure.